Foresight on land-based mass transport system - Dulay, Erik Karlo (Technology Management Center, 2014)
Metro Manila traffic conditions are at its critical level, which creates a negative impact on productivity and sustainability. The present scheme of land-based transport system i.e. bus jeepney, and e-jeepney a.k.a. Comet are the major modes of transportation in the metro, and are being supplemented by the Metro Rail and Light Rail systems laid out on the major highways. The sheer number of the land-based vehicles compounded by the inefficient traffic and road use aggravates the condition of traffic in city. Metro Manila traffic congestion is expected to reach capacity of greater than 1.5 ratio of traffic volume over road capacity - like filling a 1 liter jar with 1.5 liters of water - by 2030 according to research published by Japan International Cooperation Agency (JICA). Metro Manila hosts more than two million motor vehicles in 2013 and grew an average of 2.13 percent per year according to the Land Transportation Office (LTO). The public transport system served around 12 million people this year (2014) and is expected to grow to 14 million by 2030. Metro Manila contributes about 36 percent of the country's GDP and is the center of the country's economic activity; it is estimated that The Philippines loses about 2.4 billion pesos a day because of transport inefficiencies. This Land-based Transportation Foresight for Metro Manila is a comprehensive study of the possible scenarios that may directly impact the metro's urban planning and complement the existing metro rail technology. This paper includes a detailed report on current land-based transportation system, environmental scan, and variables and uncertainties that affect the subject. The rail system is out of scope.